Rosa laevigata Michx. Polysaccharide Ameliorates Diabetic Nephropathy in Mice through Inhibiting Ferroptosis and PI3K/AKT Pathway-Mediated Apoptosis and Modulating Tryptophan Metabolism - Tianyu Zhang; Wenjuan Sun; Lixin Wang; Hui Zhang; Yuansong Wang; Baochao Pan; Hanzhou Li; Ziang Ma; Kai Xu; Huantian Cui; Shuquan Lv (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a metabolic disease wherein chronic hyperglycemia triggers various renal cell dysfunctions, eventually leading to progressive kidney failure. Rosa laevigata Michx. is a traditional Chinese herbal medicine. Many studies have confirmed its antioxidative, anti-inflammatory, and renoprotective effects. However, the effects and mechanisms of Rosa laevigata Michx. polysaccharide (RLP) in DN remain unclear. In this study, a DN mouse model was established to investigate the therapeutic effect of RLP on DN mice. Then, nontargeted metabolomics was used to analyze the potential mechanism of RLP in the treatment of DN. Finally, the effects of RLP on ferroptosis and the PI3K/AKT pathway were investigated. The results demonstrated that RLP effectively alleviated renal injury and reduced inflammation and oxidative stress in the kidney. In addition, nontargeted metabolomic analysis indicated that RLP could modulate riboflavin metabolism and tryptophan metabolism in DN mice. Notably, ferroptosis and PI3K/AKT pathway-mediated apoptosis in the kidney were also ameliorated following RLP treatment. In conclusion, this study confirmed that RLP had a significant therapeutic effect on DN mice. Furthermore, RLP treatment modulated tryptophan metabolism and inhibited ferroptosis and PI3K/AKT pathway-mediated apoptosis in the kidney.